Implementation of Quantitative Decision Aids in the Oklahoma Probation and Parole System, 1989-1990 - Schneider, Anne L. ([Verlag nicht ermittelbar], 1993)
These data were collected to examine the use of quantitative decision aids in making probation and parole decisions in Oklahoma. The quantitative aids implemented in Oklahoma were modifications of the Wisconsin risks/needs assessment instruments. To determine the uses of and attitudes towards such instruments, Oklahoma probation and parole officers were queried regarding the appropriateness of the instruments in making probation and parole decisions, the specific circumstances in which the instruments were useful, the reasons why the instruments were used, and the extent to which the instruments were manipulated. In addition, data were collected from the officers on job satisfaction and age, length of employment, sex, education, and race.